Modification of nonroach for the discharge sustained by surface waves in the range of the low pressure - Azarenkov, N.A.; Gushchin, Vl.V.; Gushchin, V.V. (Вопросы атомной науки и техники, 2005)
In the low pressure region, when the electron mean free path is larger then the discharge size, electron dynamics becomes nonlocal and nonequilibrium. In the present work, the self-consistent set of the equations, which take into account anomalous skin-effect, is received. It consists of the kinetic equation for electron energy distribution function (EEDF), nonlocal Maxwell equations and the equations of ion hydrodynamics. In expressions for power diffusion, "bounce" electrons are taken into account, which are responsible for anomalous skin - effect. The determining role of these effects in maintenance of the discharge sustained by surface waves are predicted in the low pressure region. В області низьких тисків, коли довжина вільного пробігу електронів більша за розмір розряду, електронна динаміка стає нелокальною та нерівноважною. Отримана самоузгоджена система рівнянь, яка враховує аномальний скін-ефект. Вона складається з кінетичного рівняння для функції розподілу електронів по енергіям, нелокальних рівнянь Максвелла і рівнянь іонної гідродинаміки. У виразах для енергетичної дифузії враховані “bounce” електрони, що відповідають за аномальний скін-ефект. Передвіщена провідна роль цих ефектів у визначенні параметрів розряду, що підтримуються поверхневими хвилями в області низьких тисків. В области низких давлений, когда длина свободного пробега электронов больше размера разряда, электронная динамика становится нелокальной и неравновесной. Получена самосогласованная система уравнений, учитывающая аномальный скин-эффект. Она состоит из кинетического уравнения для функции распределения электронов по энергиям, нелокальных уравнений Максвелла и уравнений ионной гидродинамики. В выражения для энергетической диффузии учтены “bounce” электроны, ответственные за аномальный скин-эффект. Предсказана определяющая роль этих эффектов в определении параметров разряда, поддерживаемого поверхностными волнами в области низких давлений.